KOMUNITAS ANAK PUNK DAN ANOMALI SOSIAL (Studi Kasus di Kecamatan Ujung Berung Kota Bandung) - Chotim, Endah Ratnawaty; Latifah, Siti Umi (Faculty of SociaI and Political Sciences (FISIP), Universitas Islam Negeri (UIN) Bandung, 2018)
This paper examines the Punk community in Ujung Berung Subdistrict, Bandung. In its coexistent life, the punk community for the wider community is regarded as aberrant behavior or social anomaly. This community is synonymous with violence, hooliganism, and no rules. This deviant behavior is considered to be disturbing to society. This act is very disturbing comfort in the social environment of society. The Punk community has had its own subculture recognized by the community and is sometimes considered perverted. Punk as a subculture form certainly has conflicting values because this subculture emerges as a form of counterculture of the mainstream social system. Referred to as mainstream is the dominant and conventional social patterns. This difference can lead to a perverted assumption from the public about the punk subculture.